2023
DOI: 10.1177/09567976231155870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Stress on Rigid Learning, Flexible Learning, and Value-Based Decision-Making in Spatial Navigation

Abstract: The current study investigated how stress affects value-based decision-making during spatial navigation and different types of learning underlying decisions. Eighty-two adult participants (42 females) first learned to find object locations in a virtual environment from a fixed starting location (rigid learning) and then to find the same objects from unpredictable starting locations (flexible learning). Participants then decided whether to reach goal objects from the fixed or unpredictable starting location. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Factors modulating stress effects. Given that stress effects can differ by sex (e.g., Espin et al, 2013;Guenzel et al, 2014;He et al, 2023) and glucocorticoids may drive stress effects on episodic memory and statistical learning (Goldfarb, 2019;Bahtiyar et al, 2020), we additionally explored whether learning under stress differed with sex and/or cortisol. We thus ran models predicting each behavior as a function of group, cortisol (see "learning-concurrent" cortisol computation below), and sex, as well as group x cortisol and group x sex interactions.…”
Section: Analysis Approachmentioning
confidence: 99%
“…Factors modulating stress effects. Given that stress effects can differ by sex (e.g., Espin et al, 2013;Guenzel et al, 2014;He et al, 2023) and glucocorticoids may drive stress effects on episodic memory and statistical learning (Goldfarb, 2019;Bahtiyar et al, 2020), we additionally explored whether learning under stress differed with sex and/or cortisol. We thus ran models predicting each behavior as a function of group, cortisol (see "learning-concurrent" cortisol computation below), and sex, as well as group x cortisol and group x sex interactions.…”
Section: Analysis Approachmentioning
confidence: 99%
“…These discrepancies likely arise from variations in stress induction methods, timing of stress induction, and performance metrics. First, past studies employed a variety of stressors, ranging from the Trier Social Stressor (the participant is interviewed by unfriendly confederates 9 , 10 ), to cold pressor (the participant places their feet in a bucket of ice water 11 , 12 ), physical fatigue 13 , threat of electric shock 14 , 15 , time pressure 16 , 17 , monetary loss 18 , and virtual fire 19 , 20 . Second, whereas some studies induced stress during navigation 14 , 16 , 18 , others induced stress post-learning but pre-navigation 13 .…”
Section: Introductionmentioning
confidence: 99%
“…There is little systematic analysis of the role of coping ability in affective decisions during IGT performance. Stress in uences a shift from a exible learning process towards more automatic forms of control and an increase in risky choices [11,12]. It has also been suggested that stress facilitates a shift toward inaction [13].…”
Section: Introductionmentioning
confidence: 99%